Mutans Streptococci Oral Colonization in 12-30-month-old Brazilian Children over a One-year Follow-up Period - Renata 0. Mattos-Graner, PhD; Maria Salete N. p. Corrga, PhD: Maria do Rosdrio de 0. Latorre, PhD; (Blackwell Synergy, 2001)
The infection levels of mutans streptococci were investigated during a one-year follow-up in children aged 12 to 30 months attending school nurseries where a sucrose-rich diet was provided.